2021
DOI: 10.1002/aepp.13214
|View full text |Cite
|
Sign up to set email alerts
|

Machine learning for food security: Principles for transparency and usability

Abstract: Machine learning (ML) holds potential to predict hunger crises before they occur. Yet, ML models embed crucial choices that affect their utility. We develop a prototype model to predict food insecurity across three countries in sub‐Saharan Africa. Readily available data on prices, assets, and weather all influence our model predictions. Our model obtains 55%–84% accuracy, substantially outperforming both a logit and ML models using only time and location. We highlight key principles for transparency and demons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…However, the other employed models showed an acceptable performance rate, while KNN reported the lowest accuracy rate of all. Our results were found to be consistent with other studies that used ML in predicting FI and con rmed the feasibility of ML use in identifying FI (41,(50)(51)(52) . The models in this study reported accuracy rates ranging from 70-82%, while other models reviewed from previous research reported accuracy rates ranging from 55-85%.…”
Section: Discussionsupporting
confidence: 91%
“…However, the other employed models showed an acceptable performance rate, while KNN reported the lowest accuracy rate of all. Our results were found to be consistent with other studies that used ML in predicting FI and con rmed the feasibility of ML use in identifying FI (41,(50)(51)(52) . The models in this study reported accuracy rates ranging from 70-82%, while other models reviewed from previous research reported accuracy rates ranging from 55-85%.…”
Section: Discussionsupporting
confidence: 91%
“…Third, our model effectively captures across‐time changes in consumption expenditure for ultra‐poor communities in Uganda. Our study is the first attempt to predict future‐period consumption expenditure at the community level; it adds to the emerging literature that relies on machine learning methods and publicly available data to predict future‐period wealth index, malnutrition, and food insecurity (Browne et al, 2021; Yeh et al, 2020; Zhou et al, 2021).…”
mentioning
confidence: 99%
“…Finally, we would strive to involve the field experts, like the owner and the administrative staff, during the second iteration to incorporate their feedback and their domain knowledge. This could uncover aspects we might have missed in the initial model (Hannon et al 2019;Zhou et al 2022).…”
Section: Discussion and Limitationsmentioning
confidence: 99%